A study of the relationship between aerobic and anaerobic capacities and speed endurance in junior football players under 19 years old - Seghiri, Rabah (sports creativity, 2025)
There is no doubt and it is noticeable that there is continuous development day after day in all sports, whether individual or team, especially football, given the popularity it enjoys among followers, coaches, and practitioners. It has also become taught in its own schools. From the time a player is in the prime of his childhood, all hopes are pinned on him to become a world-class star, due to scientific development, sports technology, and sports coaches in all specialties, whether administrators, coaches, doctors, or psychological and physical trainers, especially those in charge of the selection and guidance process. Each category has its own special characteristics. This is according to his chronological, skeletal, and biological age. The coach or physical trainer must take this into account because any defect, whether in promoting the player to the next category because he has a greater physique and muscle density than his peers, is not a successful indicator. This may pose a danger to his football career, even though he may perform well in the first seasons, but he will not continue in this way because there is a defect in the player's qualification process, training programs, or player selection and guidance according to the various playing positions, with the differences and multiplicity of playing plans. The World Cup, the biggest football event, is the cradle of the emergence of all new plans and playing methods. This specialized selection and guidance in football is done at the level of skill and morphological elements at the beginning, and some physiological and physical indicators that have become among the most important elements that football depends on and are taken into consideration in the selection and guidance process or building training units at the beginning of seasons or from one competition to another and from one match to another, even from one player to another, although football does not depend on a specific aspect or characteristic, but has come to include all aspects. Since modern football relies on speed, accuracy, and focus throughout the match, a football player must possess high physical and physiological qualities to keep pace with the game's dynamics. These dynamics involve rapid transitions from one position to another, from defense to attack and vice versa, in a very short time. The player's running speed ranges from slow to medium to fast to very fast, whether in a straight line or in a curved pattern, including turning and twisting. All these skills and movements are linked to the maturation and development of the motor, morphological (organic), and physiological (functional) aspects. These aspects are complementary; rapid, continuous, high-intensity movement is only possible with the complete development of the musculoskeletal system, muscles, and bones, and a low percentage of body fat. Likewise, the ability to produce energy, which is either aerobic or anaerobic. It can be said that it is necessary for a football player to have good aerobic and anaerobic abilities because football is not like other sports that depend on one system for energy production. Aerobic abilities are the basis for aerobic energy production, as they are more related to general endurance. Anaerobic abilities are among the basics of the lactic acid system and the anaerobic phosphate system, through which the player's performance level and physical gains can be known, especially specific endurance. Endurance is divided into three sections: (strength endurance, performance endurance, and speed endurance). The latter, i.e., maintaining speed, is a characteristic and feature of the modern football player. It is a combination of endurance and speed, in addition to strength, i.e., the characteristics specific to football. Dr. Hashem Yasser Hassan believes that during (90) minutes, players run at different speeds from (5200m) to (7800m), of which (1330m) to (2700m) are at maximum speed and less than maximum. Some studies, after analyzing the movements of players in ten consecutive matches with one team, showed the following results: Midfielders cover a distance of 1000m to 1200m, attacking players cover a distance of 850m to 1100m, and defensive players cover a distance of 600m to 800m. As for the speed that players perform using the ball in general, it reaches (40m-60m), and the running distance without the ball reaches (50m-80m). As for the number of different distance sprints, it is (50-70) sprints, and (260-350) different jumping and falling movements.